2010
DOI: 10.1017/s0033291710001443
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns of deficits in visuospatial memory and executive function in patients with major depression with and without ECT referral

Abstract: A double dissociation emerged from the comparison of cognitive profiles of ECT and NECT patients. ECTs showed executive deficits, particularly in attentional flexibility, but mild deficits in tests of visuospatial memory. NECTs presented the opposite pattern. This suggests predominantly frontostriatal involvement in ECT versus temporal involvement in NECT depressives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 79 publications
2
12
0
Order By: Relevance
“…Patients' memory was objectively assessed using a popular and regularly used global measure of cognition (MMSE), a standardized neuropsychological test of visuospatial memory (CANTAB SRM), while changes in their subjective memory were monitored using another commonly used measure (SSMQ) and a further questionnaire not previously used in this population (PRMQ). Despite its wide use in psychiatric practice our results concur with the criticisms offered by others that the MMSE does not have the sensitivity to detect the deficits associated with ECT (Robertson & Pryor, 2006;Falconer et al 2010;Tsaltas et al 2011). This result is important for two reasons.…”
Section: Discussionsupporting
confidence: 88%
“…Patients' memory was objectively assessed using a popular and regularly used global measure of cognition (MMSE), a standardized neuropsychological test of visuospatial memory (CANTAB SRM), while changes in their subjective memory were monitored using another commonly used measure (SSMQ) and a further questionnaire not previously used in this population (PRMQ). Despite its wide use in psychiatric practice our results concur with the criticisms offered by others that the MMSE does not have the sensitivity to detect the deficits associated with ECT (Robertson & Pryor, 2006;Falconer et al 2010;Tsaltas et al 2011). This result is important for two reasons.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore fMRI studies demonstrate heightened amygdala activity in depression [16,17,36]. Even positive social feedback in depressed individuals elicits an increase in amygdala fMRI signal which is not seen in normal controls [18].…”
Section: Amygdala Dysfunction As a Precursor To Depression: Molecularmentioning
confidence: 97%
“…While executive function is compromised in depressed patients neither verbal learning visual spatial memory delay recall recognition memory nor other memory domains of the temporal cortex and hippocampus appear to be so at risk [16,17].…”
Section: Diminished Executive Function In Depressionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported that individuals referred for ECT due to drug-resistant depression, when matched and compared with those with depression but not referred for ECT, produced different cognitive profiles. 38 The former were weaker on executive tasks, the latter on memory, suggesting subtypes of depressives with dissimilar baseline cognitive profiles to begin with. Numbers were small ( n =15 in each group) and all were female.…”
Section: Cognitive Changementioning
confidence: 99%